Penanaman Kelapa Sawit Sebagai Ancaman Ekologis dalam Perspektif Hukum Lingkungan - Ade Lukman Firmansyah; Fahmi Nuraziz Awaludin; Dewi Mayang; Tansya Hadiansyah Ramdi; Yoga Ammar Arifin (Journal of Legal, Political, and Humanistic Inquiry, 2025)
This study examines oil palm cultivation as an ecological threat from the perspective of environmental law, focusing on the paradoxical role of the state in regulating and promoting plantation expansion. Using a normative juridical approach with descriptive-analytical methods, the research analyzes statutory regulations, environmental law principles, and policy frameworks governing oil palm plantations and environmental protection. The findings indicate a structural contradiction between the state’s constitutional obligation to protect the environment and its economic policies that actively encourage oil palm expansion. Although environmental law instruments, including environmental permits and environmental impact assessments, are formally established to prevent ecological degradation, their implementation remains largely procedural and weakly enforced. This condition contributes to deforestation, biodiversity loss, water pollution, and social-ecological conflicts affecting local communities. The study reveals that the dominance of economic interests has positioned environmental protection as subordinate within development policy.